(untitled) (International journal of artificial intelligence, 2026)
Transport corridors are essential to the functioning of modern economies, enabling the efficient movement of goods across domestic and international markets. In the United States, railway corridors represent a key component of the national transport system, supporting large-scale freight operations and supply chain integration. This article examines the structure and role of railway transport corridors in the United States, with particular emphasis on their contribution to long-distance transportation, intermodal connectivity, and logistics efficiency. It also considers their interaction with other transport modes and the challenges affecting their performance. The study concludes that railway corridors remain a strategically important element of the U.S. transport infrastructure, significantly contributing to economic development and global trade connectivity.